The influence of status on satisfaction with relative rewards - Albrecht, Konstanze; von Essen, Emma; Fliessbach, Klaus; Falk, Armin (Frontiers in Psychology, 2013)
This study investigates how induced relative status affects satisfaction with different relative payoffs. We find that participants with lower status are more satisfied with disadvantageous payoff inequalities than equal or higher status participants. In contrast, when receiving an advantageous payoff, status does not affect satisfaction. Our findings suggest that relative social status has important implications for the acceptance of income inequalities.